Publicly funded practice-oriented clinical trials: of importance for healthcare payers. (November 2016) - Neyt, Mattias; Christiaens, Thierry; Demotes, Jacques; Walley, Tom; Hulstaert, Frank
Aim: Many questions of relevance to patients/society are not answered by industry-sponsored clinical trials. We consider whether there are benefits to governments in funding practice-oriented clinical trials.Methodology: A literature search including publications on institutions' websites was performed and supplemented with information gathered from (inter)national stakeholders.Results: Areas were identified where public funding of clinical trials is of importance for society, such as head-to-head comparisons or medical areas where companies have no motivation to invest. The available literature suggests publicly funded research programs could provide a positive return on investment. The main hurdles (e.g., sufficient funding and absence of equipoise) and success factors (e.g., selection of research questions and research infrastructure) for the successful conduct of publicly funded trials were identified.Conclusion: Governments should see public funding of pragmatic practice-oriented clinical trials as a good opportunity to improve the selection and quality of treatments and stimulate efficient use of limited resources.